Harnessing AI in Precision Agriculture for Sustainable Kiwifruit Farming - Theofanis Kalampokas; Eleni Vrochidou; Maria Tzampazaki; George A. Papakostas (Journal of Communications Software and Systems)
Sustainable green kiwifruit production is related to enhanced fruit quality and decreased farming costs. As kiwifruit farming becomes more popular and commercialized, precision agriculture (PA) practices are adopted towards its digital and green transformation. In this work, the application of artificial intelligence (AI) in PA of kiwifruit farming is investigated, by analyzing existing applications, current research and digital innovations. This work aims to identify on a practical level all current implementations of AI in kiwifruit farming and provide a feasibility analysis for the practical application of the most current and promising AI innovations on site. Research findings are analyzed towards capturing the broad range of current status and perspectives of AI in kiwifruit farming, as well as to identify research gaps, so as to guide further beyond the green and digital transformation of the kiwifruit industry.